Analisis Kelayakan Usaha dan Titik Impas Agroindustri Tape Singkong - Setiawan, Imam; Arifin, Samsul (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2024)
This study aims to determine the cost, revenue, and income, determine the R/C value and break-even point of the cassava tape agro-industry business in Gandamekar Village, Kadungora District, Garut Regency. The research using the census method. The number of cassava tape craftsmen is 12 people. The data obtained were analyzed quantitatively and carried out in one production process. The results showed that: The cost of the cassava tape agroindustry in Gandamekar Village in one production process averaged IDR. 440,313.83 and the average revenue was Rp. 628,333.33 so that the average income earned by the artisans was Rp. IDR. 188,035.35 in one production process. The R/C value of the cassava tape agro-industry business in Gandamekar Village is R/C ratio = 1.42 for every cost incurred of IDR 1, you will get a profit of IDR 0.42. (3) The break-even point for the cassava tape agroindustry  revenue point is IDR. 10,421.06, the price break-even point is IDR.5,857.36 and the average production volume break-even point is 52.67 kg.